Keanekaragam Jenis Udang di Muara Namhoi Kecamatan Mempawah Hilir Kabupaten Mempawah, Kalimantan Barat - Maulani, Tari; Padmarsari, Widadi (Department of Aquatic Resource Management, Faculty of Agriculture, Universitas Tanjungpura, 2024)
ABSTRACTShrimp are members of the Crustacea subphylum which can be found in fresh waters to marine waters. Shrimp diversity is very important to know, especially in the Namhoi Estuary which is an active fishing area for both fish and shrimp. The aim of the research is to determine the diversity of shrimp in Muara Namhoi which includes relative abundance, diversity index, uniformity index, dominance index and environmental parameters. The research was carried out for ± 2 months, namely July